Functional equation

For students of class 11-12 (age 16+)
Posts: 1
Joined: Thu Apr 09, 2015 6:22 pm

Functional equation

Unread post by joy_li » Thu Apr 09, 2015 6:45 pm

I tried to solve $f(x-y)=f(x)+f(y)$ and found $f(x) = -cx$
(the process i followed is in the first comment)
but this gives
$-c(x-y) = -cx-cy$
$\Rightarrow -c(x-y) \neq -cx-cy $
someone please help me where did i go wrong :cry:

User avatar
Posts: 268
Joined: Tue Dec 07, 2010 7:38 pm
Location: Dhaka, Bangladesh or Cambridge, UK

Re: Functional equation

Unread post by nayel » Wed Apr 15, 2015 12:43 am

joy_li wrote:$\Rightarrow -c(x-y) \neq -cx-cy$
Why? What if $c=0$?
"Everything should be made as simple as possible, but not simpler." - Albert Einstein

Post Reply